Chemically modified microRNA delivery via DNA tetrahedral frameworks for dental pulp regeneration - Wei, Xiaoling; Xu, Huaxing; Zhou, Mengqi; Zhou, Qiangqiang; Li, Mingqiang; Liu, Yuehua (Journal of nanobiotechnology, 2024)
Dental pulp regeneration is a promising strategy for addressing tooth disorders. Incorporating this strategy involves the fundamental challenge of establishing functional vascular networks using dental pulp stem cells (DPSCs) to support tissue regeneration. Current therapeutic approaches lack efficient and stable methods for activating DPSCs. In the study, we used a chemically modified microRNA (miRNA)-loaded tetrahedral-framework nucleic acid nanostructure to promote DPSC-mediated angiogenesis and dental pulp regeneration. Incorporating chemically modified miR-126-3p into tetrahedral DNA nanostructures (miR@TDNs) represents a notable advancement in the stability and efficacy of miRNA delivery into DPSCs. These nanostructures enhanced DPSC proliferation, migration, and upregulated angiogenesis-related genes, enhancing their paracrine signaling effects on endothelial cells. This enhanced effect was substantiated by improvements in endothelial cell tube formation, migration, and gene expression. Moreover, in vivo investigations employing matrigel plug assays and ectopic dental pulp transplantation confirmed the potential of miR@TDNs in promoting angiogenesis and facilitating dental pulp regeneration. Our findings demonstrated the potential of chemically modified miRNA-loaded nucleic acid nanostructures in enhancing DPSC-mediated angiogenesis and supporting dental pulp regeneration. These results highlighted the promising role of chemically modified nucleic acid-based delivery systems as therapeutic agents in regenerative dentistry and tissue engineering. Graphical abstract